(untitled) (Scientific journal of the Fergana State University, 2026)
Landslide-dammed lakes are widespread in mountainous regions and represent one of the most significant natural sources of catastrophic flooding. Forecasting the potential failure of their dams and determining the level of hazard are among the most crucial tasks in limnology. This article systematizes approaches to flood risk assessment for dammed lakes by establishing a direct correlation between the genetic type of the dam and its stability against hydrodynamic and seismic processes. Based on an analysis of regional data from Central Asia (Sarez, Sary-Chelek, and Iskanderkul lakes) and contemporary global geomorphological stability indices (SI, DBI, HDSI) from the Scopus database, a three-category risk classification is proposed. According to this classification, glaciogenic dams (moraine cores) are assigned to the highest risk category due to their susceptibility to piping (suffosion washout/internal erosion) and thermal degradation. Gravitational dams (rockslide-landslide dams), despite their large size, require stability assessment based on the ratio of the dam volume to the watershed area. The presented genetic-geomorphological framework allows for the development of scientifically sound, priority measures for mudflow hazard mitigation even under conditions of scarce operational data.